Network analysis and traceability on Bitcoin blockchain - Phung, Minh Khanh (Nanyang Technological University, 2022)
Over the last few years, ransomware has thrived and become one of the dominant threats in cyberspace. It has targeted various public organizations and businesses of all sizes and across industries, aiming to exploit personal benefits and destroy the backbone of the economy. Ransomware evolved into many different formats and leveraged numerous anonymization techniques, including the abuse of cryptocurrency to launder the payment. Bitcoin, the most popular virtual currency, has been known as the primary payment mechanism for such fraudulent activities. Thus, in this study, we want to propose an entire data-driven process to detect new ransomware family that involved in Bitcoin transactions from public data sources. Furthermore, we also investigate the Bitcoin spending patterns and analyze the financial impacts of two ransomware attacks that were uncovered in our experiment.